Metabolic disposition of AZD8931, an oral equipotent inhibitor of EGFR, HER2 and HER3 signalling, in rat, dog and man. (December 2014) - Ballard, Peter; Swaisland, Helen C.; Malone, Michael D.; Sarda, Sunil; Ghiorghiu, Serban; Wilbraham, Darren
Abstract 1. This series of studies in rats, dogs and humans (Clinicaltrials.gov identifier: NCT01284595) investigated the pharmacokinetics, tissue distribution, metabolism and excretion of the EGFR, HER2 and HER3 signalling inhibitor AZD8931. 2. Single oral or intravenous doses of 2-(4-[4-(3-chloro-2-fluoro[U-14C]-phenylamino)-7-methoxy-quinazolin-6-yloxy]-piperidin-1-yl)-N-methyl-acetamide difumarate ([14C]-AZD8931) were administered. 3. AZD8931 absorption was rapid in all species. Following [14C]-AZD8931 administration to rats, radioactivity was widely and rapidly distributed, with the highest levels in organs of metabolism and excretion (gastrointestinal tract, liver). Following oral and intravenous [14C]-AZD8931 administration, excretion of radioactivity by all species occurred predominantly via the bile into faeces, with <5% of the dose being eliminated in urine. In all species, AZD8931 was principally cleared by metabolism. The major route of metabolism was hydroxylation and O-demethylation in rat, and aryl ring oxidation in dog. Metabolism of AZD8931 in humans was attributed to three pathways; oxidation and amine or ether cleavage around the piperidine ring with subsequent glucuronide or sulphate conjugation. 4. AZD8931 is largely cleared by metabolism in the rat, dog and human. Excretory profiles indicate that there are no unique human metabolites.